1996
DOI: 10.1021/bi960785e
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Long-Chain Chimeric Human Acyl-CoA Dehydrogenase:  Medium-Chain Enzyme with the Active Center Base Arrangement of Long-Chain Acyl-CoA Dehydrogenase

Abstract: The catalytically essential glutamate residue that initiates catalysis by abstracting the substrate R-hydrogen as H + is located at position 376 (mature MCADH numbering) on loop JK in medium chain acyl-CoA dehydrogenase (MCADH). In long chain acyl-CoA dehydrogenase (LCADH) and isovalerylCoA dehydrogenase (IVDH), the corresponding Glu carrying out the same function is placed at position 255 on the adjacent helix G. These glutamates thus act on substrate approaching from two opposite regions at the active center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
77
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 26 publications
(67 reference statements)
14
77
2
Order By: Relevance
“…Nevertheless, the above data show that subtle variations in active site topology determine the outcome of the enzyme stereospecificity and reinforce the idea that inversion of enantioselectivity can be generally carried out without major structural reconstruction (36). Our results are also in line with studies from medium-chain acyl-CoA dehydrogenase, where it was demonstrated that a functional glutamate involved in substrate dehydrogenation can be relocated in the enzyme active site by a double amino acid substitution (37,38). The results presented here underline the important role of acidic residues for the function of VAO.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the above data show that subtle variations in active site topology determine the outcome of the enzyme stereospecificity and reinforce the idea that inversion of enantioselectivity can be generally carried out without major structural reconstruction (36). Our results are also in line with studies from medium-chain acyl-CoA dehydrogenase, where it was demonstrated that a functional glutamate involved in substrate dehydrogenation can be relocated in the enzyme active site by a double amino acid substitution (37,38). The results presented here underline the important role of acidic residues for the function of VAO.…”
Section: Discussionsupporting
confidence: 89%
“…Although it is not possible to determine the exact occupancies of the bound ligand in the crystal structures of each complex due to the relatively lower resolution, it is evident, from the levels of electron densities in the final 2F o -F c maps and the refined temperature factors, that the occupancies of the bound ligands in the C12-and C14-CoA complexes are much lower than that of the C8-CoA complex, again implying that the longer product (C12-and C14-CoA) binds less tightly to (or dissociates more easily from) the enzyme. Furthermore, the charge transfer complex formed between MLCADH with 3-thiaoctanoyl-CoA is less stable compared to that between MCADH with the substrate analog (Nandy et al, 1996). Again, the stability of the charge transfer complex is probably directly related to the binding energy of the analog to the active site of the enzyme.…”
Section: Discussionmentioning
confidence: 94%
“…The "extra space" in the active site cavity is generated by the protein in the case of MLCADH, whereas it is from the lack of the carbonyl oxygen of the bound ligand in the thioether complex. On the other hand, the dramatic increase in the oxygen reactivity with substrate longer than C10-CoA observed in both the wild type and MLCADH can be directly correlated with the product dissociation (Srivastava et al, 1995;Nandy et al, 1996). Although it is not possible to determine the exact occupancies of the bound ligand in the crystal structures of each complex due to the relatively lower resolution, it is evident, from the levels of electron densities in the final 2F o -F c maps and the refined temperature factors, that the occupancies of the bound ligands in the C12-and C14-CoA complexes are much lower than that of the C8-CoA complex, again implying that the longer product (C12-and C14-CoA) binds less tightly to (or dissociates more easily from) the enzyme.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations